2007
DOI: 10.1017/s0954102007000235
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the origins of crustaceans of Antarctic lakes

Abstract: New evidence regarding the origins of the Crustacea of Antarctic lakes is reviewed. Palaeolimnological data indicates that the cladoceran Daphniopsis studeri has been present in Lake Reid, Larsemann Hills, for over 120 000 yr. This is the first direct evidence of a continental lacustrine refugium during the last glacial maximum. There are strong indications that the calanoid copepod Boeckella poppei maintained populations over the same period in lakes of the Amery Oasis, and the rapid post-glacial colonization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
0
36
1
Order By: Relevance
“…It is significant that Macrothrix oviformis together with Daphnia studeri are the only two species of the Cladocera present in continental Antarctica (the former is found only on the Antarctic Peninsula). Even during the Last Glacial Maximum, some refugia of the freshwater fauna existed on the Antarctic continent (Cromer et al 2006;Gibson and Bayly 2007), so we can assume that these continental populations of Daphnia and Macrothrix were not recently introduced, but existed from a pre-glacial time. At the same time, some other territories, i.e.…”
Section: Biogeographymentioning
confidence: 99%
See 1 more Smart Citation
“…It is significant that Macrothrix oviformis together with Daphnia studeri are the only two species of the Cladocera present in continental Antarctica (the former is found only on the Antarctic Peninsula). Even during the Last Glacial Maximum, some refugia of the freshwater fauna existed on the Antarctic continent (Cromer et al 2006;Gibson and Bayly 2007), so we can assume that these continental populations of Daphnia and Macrothrix were not recently introduced, but existed from a pre-glacial time. At the same time, some other territories, i.e.…”
Section: Biogeographymentioning
confidence: 99%
“…Only two species of Cladocera can be definitively regarded as widely distributed in the Subantarctic, Alona weinecki and Daphnia studeri (Frey 1988;Pugh et al 2002;Benzie 2005;Gibson and Bayly 2007). The status of populations of Chydorus cf.…”
Section: Biogeographymentioning
confidence: 99%
“…The different responses to temperature recorded could refiect species-specific adaptations. South American species of Boeckella are mostly distributed in lakes and ponds of Patagonia which are temperate or cold environments Gibson & Bayly, 2007;Persaud et al, 2007;Adamowicz et al, 2010). In particular, the cold stenotherm condition of B. brevicaudata can also be inferred from its restricted spatial and/or temporal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Such environments are dominated by copepods of the genus Boeckella (cf. Bayly, 1992;Marinone et al, 2006), which are cold stenotherm (Gibson & Bayly, 2007;Adamowicz et al, 2010), and display combined strategies to cope with high ambient UV levels (Zagarese et al, 1997;Alonso et al, 2004;Tartarotti et al, 2004;Marinone et al, 2006;Tartarotti & Sommaruga, 2006). These strategies include diel vertical migration in lakes where depth can constitute a refuge; the acquisition of photo-protective compounds (mycosporine-like amino acids and carotenoids), and photo-enzymatic repair (Zagarese et al, 1997;Tartarotti et al, 1999;Alonso et al, 2004;Garcia et al, 2010;Perez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This approach allowed the characterization of copepod species in sediments from three fresh to brackish Antarctic lakes as old as 10 ka BP. In most cases, the fossil species found matched those of extant lake populations, but analysis of early-to mid-Holocene sediments from one lake revealed a species that is not known to exist today (Gibson and Bayly, 2007). It was furthermore shown that it is possible to recover copepod DNA from lake sediments that underwent long-term refrigeration (4°C) or preservation in polyethyleneglycol .…”
Section: Fdna In Antarctic Lakes: Ancient Copepodsmentioning
confidence: 96%